Corticothalamic Projections from the Rat Primary Somatosensory Cortex - Killackey, Herbert P. (J Neurosci, 2003)
To study the cells of origin of corticothalamic inputs to the ventral posterior and posterior medial nuclei of the somatosensory thalamus in rats, we injected small aliquots of tracer into each nucleus and analyzed the pattern of retrograde labeling in the posteromedial barrel subfield of primary somatosensory cortex, which can be divided into barrel and nonbarrel zones. The ventral posterior nucleus is innervated by neurons in layer VIa of both zones, whereas the posterior medial nucleus is innervated by neurons in layers Vb and VIb of both zones with additional innervation from layer VIa of nonbarrel cortex. Thus, only the posterior medial nucleus receives a layer Vb input. Because the layer Vb input is interpreted as the initiation of a feedforward cortico-thalamocortical pathway, this implies that the target of the posterior medial nucleus, which includes the nonbarrel cortex, is a higher-order cortical area. We thus suggest that this cortical zone, which is classically considered part of the primary somatosensory cortex, should be reclassified as higher-order cortex.